NMR metabolic composition profiling of high pressure pasteurized milk preserved by hyperbaric storage at room temperature. (April 2022) - Lemos, Álvaro T.; Goodfellow, Brian J.; Delgadillo, Ivonne; Saraiva, Jorge A.
Abstract: 1 H NMR spectroscopy was used to study the effect of hyperbaric storage (HS) on the chemical composition of high pressure pasteurized milk (HPP milk). A subsequent multivariate analysis (MVA) was applied to distinguish samples stored under different conditions. Three different pressure levels (50/75/100 MPa), at naturally variable uncontrolled room temperature (≈ 20 °C), and up to 40 days of storage were compared with controls at atmospheric pressure and room temperature (AP/RT) or under refrigeration (RF). Only AP/RT samples presented spoilage compounds as lactate, methylamine and trimethylamine derived from microbial deterioration of milk. However, RF spectral profiles were closer to initial milk samples than the HS profiles, mainly in the aliphatic region which corresponds to an increase in soluble proteins for the HS samples. Additionally, MVA revealed higher levels of citrate, carnitine, lactose, and orotate in initial and RF samples, while HS samples had higher levels of acetate, N-acetylglucosamine, choline and galactose. In conclusion, although HS and RF samples were separated by MVA, there was no presence of microbial spoilage compounds in the spectra, being HS at RT an eco-friendlier alternative to preserve foods than traditional RF. Highlights: High-pressure pasteurized milk (HPP milk) presented a typical 1D 1 H NMR spectrum. Refrigerated (RF) samples were closer to the initial samples of HPP milk. Hyperbaric storage (HS) showed higher levels of acetate, choline and galactose. RF presented higher levels of citrate, carnitine, lactose and orotate. HS raised soluble protein, potentially with higher digestibility/nutritional value.